Factores de riesgo cardiovascular e índice tobillo brazo en la enfermedad arterial periférica, Pasaje - El Oro, 2016. - Cabrera Riofrío, Yessenia Amparo (2017)
According to the World Health Organization (WHO), cardiovascular diseases are the leading cause of death worldwide, Peripheral Arterial Disease (PAD), is linked to chronic comorbidities and risk factors, EAP in the world was 202 million in 2010, and has increased by 23.5%, currently considered a pandemic. In Ecuador, statistics on the diagnosis of Peripheral Arterial Disease are not known, and this leads to serious complications and even death, the ankle-brachial index (ABI), has a sensitivity of 95% and a specificity of 99% for diagnosis Of EAP. The objective is to analyze cardiovascular risk factors with peripheral arterial disease in the middle adult. A retrospective cohort study was performed in subjects exposed and not exposed to risk factors (age, sex, smoking, hypertension, DMT2, dyslipidemia, family history of cardiovascular diseases, overweight / obesity), the study population was of 6876 people aged 45 to 64 years of age from the canton Pasaje, and the sample was 187 people, we performed the ankle index arm for the diagnosis of PAD, the data were analyzed using the Chi2 statistical test, p value , V de Cramer and the OR with a 95% CI. Results: The prevalence of PAD was 27.8%, association with risk factors (Chi2: 34.28 (1gl), Cramer's V: 0.43, p: 4, 75x10-9 and OR: 14.55; IC 95%: LCi= 4.96 to LCs= 42.64). The risk factors that had association were: smoking (p: 1,17 x 10-9 / OR: 29.55; IC 95%: LCi= 6.49 to LCs= 134.51), diabetes (p: 5,4x10-5/ OR: 4.21; CI 95%: LCi= 2, 03 to LCs= 8, 72), dyslipidemia (p: 0.004 / OR 2.68, IC 95%: LCi= 1.34 to LCs= 5.32), family history (p: 4,14x10-4/ OR 3.22, IC 95%: LCi= 1.66 to LCs= 6.25), overweight / obesity (p: 9,17x10-7/ OR: 6.10; IC 95%: LCi= 2.83 to LCs= 13.19). In conclusion, the PAD has a high prevalence in our environment and cardiovascular risk factors have a strong association with the disease. Key words: peripheral arteriopathy, Yao index, average adult, cardiovascular risk.